2020
DOI: 10.1155/2020/2475930
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Bifurcation Angles in Left Main Bifurcation Intervention Using a Two-Stent Technique

Abstract: Objectives. The aim of this study was to assess the clinical impact of 3 bifurcation angles in left main (LM) bifurcation treated with the 2-stent technique. Background. Data are limited regarding the impact of bifurcation angles after LM percutaneous coronary intervention (PCI). Methods. Using patient-level 4 multicenter registries in Korea, 462 patients undergoing LM bifurcation PCI with the 2-stent technique were identified (181 crush, 167 T-stenting; 63% 1st generation drug-eluting stent (DES), 37% 2nd gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…We did not find an association between the bifurcation angle and long-term outcome in the one-stent group. In contrast, Ki et al [ 31 ] found an angle wider than 152 degrees between the PV and MB to predict TLF in LM bifurcation lesions treated with the crush technique, but not those treated with the T-stenting technique. Using this cut-off of 153 degrees, a similar relationship was observed in our registry in the non-LAD bifurcation group treated with the two-stent strategy, but not in the LAD bifurcation group treated with the same strategy ( Figure S4 ).…”
Section: Discussionmentioning
confidence: 97%
“…We did not find an association between the bifurcation angle and long-term outcome in the one-stent group. In contrast, Ki et al [ 31 ] found an angle wider than 152 degrees between the PV and MB to predict TLF in LM bifurcation lesions treated with the crush technique, but not those treated with the T-stenting technique. Using this cut-off of 153 degrees, a similar relationship was observed in our registry in the non-LAD bifurcation group treated with the two-stent strategy, but not in the LAD bifurcation group treated with the same strategy ( Figure S4 ).…”
Section: Discussionmentioning
confidence: 97%
“…not in the cases after T-stenting [55]. A greater area with low shear stress on a long metal overlapping site might be responsible for more restenosis or thrombogenic events in the group with the wider Angle C.…”
Section: Plos Onementioning
confidence: 88%
“…Ki et al investigated the impact of the BA on clinical outcomes in 462 patients treated with LMCA two-stenting in the COBIS registry [ 51 ]. A wider LMCA-LAD angle (Angle C) was an independent predictor of TLF after crush stenting with a best cut-off value of 152°, but it was not in the cases after T-stenting [ 55 ]. A greater area with low shear stress on a long metal overlapping site might be responsible for more restenosis or thrombogenic events in the group with the wider Angle C.…”
Section: Review and Discussionmentioning
confidence: 99%